Long-term evaluation of mitigation techniques used for permafrost thermal stabilization at the Beaver Creek Experimental Road Site, Yukon, Canada ... - López López, Ximena; Bilodeau, Jean-Pascal; Lemieux, Chantal; Doré, Guy (Borealis, 2025)
Soil temperature from embankment material and natural ground, measured at the Beaver Creek Experimental Road Site (Yukon, Canada). Data were measured under the center and under the slope of the embankment, at various depths: from close to the surface of the road pavement, down to 15 meters. The site is divided in 50 meters long sections with a control section and 11 techniques to mitigate permafrost degradation: various configuration of Air convection embankment and Heat drain, Snow/sun shed, Longitudinal convection culverts, Grass covered embankment, Snow clearing, and Light coloured aggregate bituminous surface treatment (BST). ... : Microsoft Excel, null ...